2011
DOI: 10.1037/a0024920
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of violent victimization on somatic symptoms among Asian American adolescents: A national longitudinal study.

Abstract: This study explored the mental health repercussions among Asian American adolescents following experiences of violent victimization. Utilizing a subsample of Asian American adolescents from Waves I and II of the National Longitudinal Study of Adolescent Health (Add Health), this study examined the relationship between violent victimization and somatic symptoms one year later, as well as moderators of this relationship. Results from a hierarchical multiple regression analysis showed that emotional bonds with fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Furthermore, the relationship between acculturation and violent victimization is in contrast to data detailed by Wu (2008). However, the current results are in accord with nonsignificant findings of acculturative measures (years spent in the United States and language spoken at home) and violent victimization by Maffini, Wong, and Shin (2011). Current outcomes also detail that additional t-tests measuring reporting based on type of victimization indicate no significance in property, violent, or any victimization models.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, the relationship between acculturation and violent victimization is in contrast to data detailed by Wu (2008). However, the current results are in accord with nonsignificant findings of acculturative measures (years spent in the United States and language spoken at home) and violent victimization by Maffini, Wong, and Shin (2011). Current outcomes also detail that additional t-tests measuring reporting based on type of victimization indicate no significance in property, violent, or any victimization models.…”
Section: Discussionsupporting
confidence: 52%
“…In this article, we adopt a broad definition of victimization to refer to a spectrum of experiences with varying degrees of severity (Maffini, Wong, & Shin, 2011). This can range from minor verbal or physical harassment to violent experiences, such as being attacked (Elias & Zins, 2003; Ho, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In a follow‐up study, Koo, Peguero, and Shekarkhar (2012) used the same data to explore the role of immigration status and gender and concluded that Asian American immigrant female students have higher odds of being threatened at school compared to White American male students. Maffini et al (2011) explored the mental repercussions among Asian American adolescents following violent victimization using the National Longitudinal Study of Adolescent Health and found that family bonds weakened the link between violent victimization and somatic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to involve parents and school staff in bullying prevention interventions for Asian Americans (Shea et al 2016). Family bonds and cohesion were found to weaken the negative effects of violent victimization and discrimination among Asian-American adolescents (Juang and Alvarez 2010;Maffini et al 2011). Furthermore, research indicates that classes with students who respect racial diversity have lower bullying incidents (Gage et al 2014).…”
Section: Develop a Bullying Prevention Programmentioning
confidence: 99%